ORAL MUCOSA - PATHOPHYSIOLOGICAL AND PHARMACOTHERAPEUTIC ASPECTS - Loredana Liliana Hurjui; Irina Gradinaru; Claudia Dorus; Daniela Maria Tanase; Adina Armencia; Ion Hurjui; Claudia Cristina Tarniceriu; Mihaela Mitrea; Ludmila Lozneanu; Carina Balcos; Ionela Lăcrămioara Șerban (Romanian Society of Oral Rehabilitation, 2022)
The oral mucosa plays an important role in the body, due to its multiple functions. The normal structure and the functions of the oral mucosa can be frequently affected, temporarily or permanently, as a result of inflammation with or without infections, physical aggression, chemical trauma, iatrogenic or other causes. The oral mucosa is involved in signaling and protecting against aero-digestive diseases and at the same time can be an indicator and evaluator (along with the smell sense) of substances that are introduced into the body voluntarily or involuntarily. No doubt that some areas such as the lingual mucosa, may in some cases reflect the general health of the digestive tract or even the body. Due to its morphological and chemical structure, the oral mucosa allows a faster diffusion, compared to the skin, of some ions and therapeutic molecules, the risk of sensitization being extremely low. Pharmacotherapy is known to be the most common and convenient way to administer drugs by swallowing. However research has shown that transmucosal absorption requires adequate blood supply to the submucosal connective tissue, a requirement that is appreciably met by the oral mucosa through the presence of abundant circulation that greatly increases the amount of substances absorbed. Taken as a whole and summarizing the functional implications of the oral mucosa, it can be concluded that this is an area of the stomatognathic system with complex roles and connections with the neighborhood and ensures a good development of digestive function, phonation and secondary to respiratory function.